2022
DOI: 10.3390/electronics11131972
|View full text |Cite
|
Sign up to set email alerts
|

Design Space of GaN Vertical Trench Junction Barrier Schottky Diodes: Comprehensive Study and Analytical Modeling

Abstract: We report gallium nitride (GaN) vertical trench junction barrier Schottky (TJBS) diodes and systematically analyzed the effects of the key design parameters on the reverse and forward characteristics of the devices. By taking advantage of the shielding effects from both the trenches and pn junctions in the TJBS structure, the high electric field at the Schottky contact region can be effectively suppressed. We found that the doping concentration, thickness, and spacing of p-GaN, as well as the depth and angle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…It is observed that the acceptor energy level of Mg is 150 meV above the valence band. Consequently, the concentration of ionized holes in GaN can be calculated by the following equation [16]:…”
Section: Simulation Detailsmentioning
confidence: 99%
“…It is observed that the acceptor energy level of Mg is 150 meV above the valence band. Consequently, the concentration of ionized holes in GaN can be calculated by the following equation [16]:…”
Section: Simulation Detailsmentioning
confidence: 99%
“…[3] Recently, the development of high-quality freestanding GaN substrates has advanced the research of GaN-based vertical power devices. [4][5][6] Compared with their lateral counterparts, vertical GaN power devices feature superior scalability and higher voltage endurance, [7][8][9][10][11][12] which is crucial for high-power-density electronic systems. Thanks to their low turn-on voltage and fast switching capability, [13] vertical GaN Schottky barrier diodes (SBDs) stand out among different types of vertical GaN power devices.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the PD logic circuit is mainly managing power for effective use by a logic decision algorithm that allocates the power to the actuator array where the shape change must be performed. The Schottky barrier diode's breakdown voltage determines each rectenna's maximum operating voltage [11,13,15]. Accordingly, the maximum voltage of the rectenna array is not enough for smart actuators.…”
Section: Introductionmentioning
confidence: 99%